Pharmacokinetics of deflazacort in rabbits after intravenous and oral administration and its interaction with erythromycin. Issue 1 (25th July 2017) - Escudero, A. I.; Marín, P.; Cárceles, C. M.; Escudero, E.
Abstract : The pharmacokinetic of deflazacort after intravenous and oral administration and the effect of erythromycin on the disposition of deflazacort in rabbits were investigated. A parallel study was carried out in twelve rabbits. The plasma concentration–time profiles of deflazacort were determined after intravenous and oral administration of single dosages of 5 mg/kg in the presence and absence (baseline) of multiple dose erythromycin regimens. Plasma concentrations of 21‐desacetyldeflazacort were determined by HPLC. Plasma concentration–time curves were analysed by compartmental pharmacokinetic and noncompartmental methods. The t ½λz values following intravenous and oral administration were 3.67 and 4.96 hr, respectively. The apparent volume of distribution at steady‐state ( V ss ) was 4.08 ± 0.31 L/kg, this value indicates that deflazacort is widely distributed into the extravascular tissues. Moreover, bioavailability after oral administration of deflazacort ( F = 87.48%) was high. Pharmacokinetic analysis after both routes of administration revealed a significant reduction in total body clearance, a significant increase in mean residence time, half‐life and plasma concentrations of the steroid in the presence of multiple dose erythromycin. The results indicated the influence of the erythromycin on deflazacort disposition, which is consistent with a pharmacokinetic‐type interaction in the elimination of the drug from the body. Moreover, this interaction should be considered to avoid adverse effects when using both drugs concomitantly.